Peningkatan Kapasitas Kader Usaha Kesehatan Sekolah (UKS) dalam Mendukung Perilaku Hidup Bersih dan Sehat di SMK Duta Mas Jakarta Barat - Fitrah Fitrah; Ratna Indra Sari; Ade Alya Safitri (Jurnal Pengabdian Ilmu Kesehatan, 2026)
The School Health Unit (UKS) is a strategic promotive-preventive program for improving student health, yet its implementation is often constrained by the limited capacity of student cadres. This community service activity aimed to strengthen the knowledge, attitudes, and skills of UKS cadres at SMK Duta Mas, West Jakarta, in supporting clean and healthy living behavior (PHBS). The method comprised socialization, participatory training, technology application (educational media and simple UKS administration formats), mentoring, and program sustainability, evaluated with a one-group pre-test post-test design involving 21 UKS cadres. Paired-sample analysis showed significant improvement in the skills domain (mean 28.71 to 33.81; p<0.001) and in the total score (mean 78.90 to 85.38; p<0.001), with 85.7% of cadres showing an increase in total score, exceeding the target indicator of 70%. Improvements in knowledge were also significant, while attitude scores, which were already high at baseline, increased only slightly. These findings indicate that participatory training effectively strengthens UKS cadre capacity and can serve as a model for sustainable school health promotion.